Factor Influencing Social Entrepreneurial Intentions - Setyawati, Harini Abrilia (JURNAL AKUNTANSI DAN MANAJEMEN, 2025)
Within Ajzen's Planned Behavior Theory framework, this article tests a model to estimate the predictors of entrepreneurial intention. We tested the entrepreneurship intention model on a sample of 100 students at a University in Indonesia. The results show that Experience significantly influences Social Entrepreneurial Intention through Moral Obligation. Individuals with more experience feel a stronger moral obligation, which positively impacts their intention to engage in social entrepreneurship. Fostering a sense of moral obligation can effectively leverage the experience of potential social entrepreneurs. The indirect effect of Experience on Social Entrepreneurial Intention through Perceived Social Support is not supported. Although experience influences perceived social support, it does not significantly impact social entrepreneurial intention. This highlights the need to better understand the role of social support in social entrepreneurship. Experience significantly influences Social Entrepreneurial Intention through Social Entrepreneurial Self-Efficacy. Experience enhances individuals’ belief in their capabilities for social entrepreneurship, influencing their intention to engage in it. Boosting self-efficacy can be a key strategy for harnessing the experience of potential social entrepreneurs.